Parodija na golemata nacionalna drama vo dramata "Balkanot ne e mrtov ili Magija edelvajs" od Dejan Dukovski - Baković, Ivica prevoditelj (2014)
The article analyses the representation of history in Dejan Dukovski's play Balcan is not Dead as postmodern version (remake) of the first Macedonian play, Vojdan Černodrinski's Macedonian Bloody Wedding. Dukovski's play could be seen as some sort of deconstruction of the myth constructed in Černodrinski's play which involves a special understanding of a Macedonian history. While Černodrinski represents Macedonian history as a circle of tragedies in which subjects are only marionettes playing already determined scenario, Dukovski is trying to represent that history from different point of view which corresponds with modern historiography. A special emphasis is put on the performances of Dukovski's play in two different socio-political contexts in the 1990s.
Projekt MZOS
Makedonski